Between reality and desire: truth and significance in Robert Lowell's "Skunk Hour" - Rodríguez Monroy, Amalia (Tropelías: Review of Literary Theory and Comparative Literature, 1995)
From a Lacanian perspective, this paper elaborates on truth as distinct from a traditional conception of the rational and as separated from the conscious intention of the author. Discourse is seen as a symbolic process in which the subject builds the figures of his unconscious desire. Nietzsche already noted the illusory nature of truth and its dependence on the metaphoric character of all forms of language as inherited beliefs whose fictive -discursive- construction we tend to forget. Our analysis of Rober Lowell's autobiographical "Skunk Hour" (Life Studies, 1957), will serve to illustrate meaning as originating in a series of textual relations; meaning as based on the capacity of tropes to displace and hide, while showing, at the same time, the fragility of our imaginary link to reality.
Keywords: Robert Lowell; truth